Inventory of heritage resources and interior routes with potential touristic in Pinos, Zacatecas - Castellanos Gutiérrez, Yaneli; Cadena Íñiguez, Jorge; Almeraya Quintero, Silvia Xochilt; Ramírez López, Artemio; Figueroa Sandoval, Benjamín (Revista Mexicana de Ciencias Agrícolas, 2019)
The inventories of heritage are instruments of management, dissemination and protection of cultural and natural assets that have a territory that can serve as a basis for formulating specific policies. The objective was to make an inventory of heritage assets with tourism potential of the municipality of Pinos, Zacatecas as an instrument for the knowledge and conservation of heritage and the proposal of tourist routes that stimulate the generation of economic income to the inhabitants of the municipality. The study was carried out in 2017 in 28 locations, to gather information and record assets, meetings were held with key informants, tours for photographic and documentary recording of assets. The classification of heritage assets was based on the proposal of the National Tourism Service of the Government of Chile (2013); Blanco et al. (2015); Parejo (2013); Navarro (2015) to catalog goods and tourism resources. 132 goods were classified into six categories that included cultural and natural heritage classified according to their hierarchy as tourist attractions. 67 surveys were applied in the municipal capital and a logistic regression was carried out to determine the influence factors on knowledge, perception and social value of the population on heritage assets. 12 tourist routes were proposed that cover the municipality of Pinos, Zacatecas concluding that the appointment of Magic Town can be extended outside the municipal seat to bring greater economic benefits to the inhabitants of the region.